A Model for Environmental Quarry System based on Particles, Vibration and Noise Components - RAISIAN, Komeil; YAHAYA, Jamaiah; DERAMAN, Aziz; HAMDAN, Abdul Razak; RAIS, Izhar Abadi Ibrahim; YAHAYA, Noor Zaitun (Journal of Environmental Management and Tourism; Vol 7 No 2 (2016): JEMT Volume VII, Issue 2(14) Summer 2016, 2016)
Environment is the surroundings in which an organization functions, including air, water, land, natural resources, flora, fauna, humans, and their interrelation. Surroundings in this context extend from within an organization to the global system. While the environmental impact refers to any change to the environment, whether adverse or beneficial, wholly or partially resulting from an organization's activities, products or services. Environmental Management System is the part of the overall management system that includes organizational structure, planning activities, responsibilities, practices, procedures, processes and resources for developing, implementing, achieving, reviewing and maintaining the environmental policy. The aim of this study is present model for environmental quarry components which are particles, Vibration and Noise (PVN) object. In addition, this study presented that noise emission sources in quarries and construction sites as being emitted from; mobile equipment, fixed processing plant and equipment, transportation (road and rail), blasting and construction and vibration main classified to Air Overpressure, ground vibration and fly rock and the last noise also dust emissions inventory for quarrying are Drilling, blasting, Handling of limestone, and Mineral processing had high significance dust emissions. To examine the model some sort of descriptive survey has been applied. According to a sort of a group’s random choosing skim, the survey sample population consisted of 285 randomly obtained from people who are living and work surrounding Langkawi Quarry (Malaysia). A significant part of the result discovered environmental quarry relate directly with research main factors such as particles, dust and vibration and its sub factors and the model be useful for environment quarry and practically environmental quarry system.
Keywords: environmental quarry model; noise; vibration; particles and dust; quarry system